The Influence of Competence and Organizational Commitment on Village Fund Management Accountability with Transparency as a Mediating Variable - Halkadri Fitra; Efrizal Syofyan; Erni Masdupi; Ery Mulyani; Salma Taqwa; Halmawati Halmawati (Universitas Negeri Padang, 2024)
This study aims to examine how competency and organizational commitment affect the accountability of village fund administration, with transparency serving as a mediating variable. Utilising a quantitative research methodology, the study distributes questionnaires to gather primary data. The research population consists of financial officers from villages around the Agam Regency, with a sample size of 92 determined using the complete sampling method. The statistical software Smart PLS version 4 is used to analyze data using Partial Least Squares (PLS). The findings indicate that the competency and transparency of civil officials have a significant impact on village fund management accountability, while organizational commitment has a non-significant positive influence. Furthermore, the mediating role of transparency between civil servants' competence, organizational commitment, and the accountability of village fund management shows an insignificant effect. This study's limitation is that it only looks at three variables. civil servants' competence, organizational commitment, and transparency in influencing the accountability of village fund management. Future research is encouraged to explore and include other variables that may affect the behavior of accountability of village fund management, to identify which variables can optimally influence the accountability of village fund management.